Porazdelitev likovnoustvarjalnih sposobnosti med osnovnošolci - Herzog, Jerneja (Revija za elementarno izobraževanje, 2008)
Distribution of Creative Art Abilities Between Pupils in Primary Schools. The article represents a portion of a broader research that dealt with connecting factors of artistic creativity and their mutual effect, which was expressed with the level of common artistic-creative abilities. In the first part, creativity in general ispresented and defined. We also threw light on the notion of artistic creativity and the factors involved in artistic creativity. The second part deals with an empirical presentation of the results of the problem-oriented research we conducted. In this research we concentrated on the similarities and differences in the results we obtained from a controlled sample. The sample was used to define the common level of artistic creativity according to the normal distribution of abilities in heterogeneous groups. The research results show that artistic-creative abilities are dispersed similarly to other abilities within the heterogeneous groups. We did not notice any difference in the distribution of artistic creativity between male and female pupils.
Keywords: artistic creativity; factors of artistic creativity; arts (crafts); primary school